'The assessment is in the chat': Analysing conversations in community care. (May 2014) - Bolger, Andrew
Home visits are a key method in social care but little is known about how they are conducted. This study analyses transcripts of audio-recordings of visits made by social care workers to their clients and contributes to an understanding of how such interactions are performed. Attention was paid to how the agenda for home visits was set through topic shifting, asking questions, interrupting and telling stories. This allowed the visits to be compared with a number of theoretical models of assessment. Variations in how workers asked questions and responded to clients' stories suggested that they had some discretion to act as street-level bureaucrats.